Monohalogenated carbamates where hydrogen bonding rules without halogen bonding: is there a link between poor carbamate crystal growth and Z′ > 1?. Issue 27 (12th June 2019) - Mocilac, Pavle; Gallagher, John F.
Abstract : Monohalogenated carbamates (CxxX ) aggregate by N–H⋯N interactions without halogen bonding and crystallise as poor quality crystalline fibres often with Z ′ > 1. Abstract : Three series of monohalophenyl- N -pyridinylcarbamate isomer grids (CxxX ) are reported (withx = para -, meta -, ortho ;X = fluorine, chlorine, bromine), andCx as the aminopyridinyl group (C5 NH4 NH–) andxX as –CO2 C6 H4 X . Nine crystal structures are presented with all nine structures aggregating via N–H⋯N intermolecular interactions as their primary hydrogen bond; as chains inCmpX, CmmX and as dimers in theCopX triad. Halogen bonding is absent and there is a preference for N–H⋯N and C–H/π⋯π stacking intermolecular interactions. Structural similarities abound with all threeCmpX structures isomorphous in space group Pc and withCopF andCopCl isomorphous in P 1̄ (No. 2). Differences between the monohalogenatedCxxX carbamates and theirCxxM andCxxOMe relatives (M, OMe = methyl, methoxy) are discussed, especially the reluctance ofCxxX to form quality single crystals as most crystallise as filamentous-like fibres under a range of crystallisation conditions. Conformational analyses of the three [3 × 3]CxxX isomer grids of minimized structures in gas-phase are detailed for comparisons with the solid-state structures. Modelling results reveal inherent steric problems inCxoX associated with bulky pendant ortho -groups ( i.e. bromine). Physicochemical analyses including melting point analysis and solid-state correlations are rationalised. A question is posed as to why theCxxX carbamates are reluctant to crystallise as quality single crystals and with a higher incidence of Z ′ > 1 in comparison with related carboxamides.